Flood risk management : research and practice: proceedings of the European conference on flood risk management research into practice (FloodRisk 2008), Oxford, UK, 30 September-2 October 2008 /: research and practice: proceedings of the European conference on flood risk management research into practice (FloodRisk 2008), Oxford, UK, 30 September-2 October 2008. (2009) - Unknown
No abstract available